Literasi Ekonomi dan Pola Perilaku Konsumsi Masyarakat Kelas Menengah ke Bawah di Era Adaptasi Kebiasaan Baru - Muhammad Hasan; Nur Arisah; Rahmatullah Rahmatullah (Universitas Winaya Mukti, 2021)
In the era of adapting to new habits, after the COVID-19 pandemic, in terms of marketing management and consumer behavior, economic literacy is very much needed in making every economic decision, including consumption. This study was conducted as an effort to explore the contribution of economic literacy to consumption behavior patterns in the new adaptation era. This study is a study with a quantitative approach. The population in this study is an active consumer society found in a number of districts/cities in South Sulawesi Province. Sampling was done purposively with criteria based on social, economic, and demographic characteristics, obtained as many as 211 respondents. The data obtained were analyzed using Structural Equation Modeling analysis. The results of this study found that economic literacy has a positive and significant influence on consumption behavior patterns in the era of adaptation to new habits.